Pengaruh Latihan Dryland Terhadap Daya Tahan Otot Atlet Renang Clavo Swimming Club - Rahman, Muhammad Taufiqul; Prawira, Asrori Yudha; 'Ala, Faridatul; Denatara, Eskar Tri; Pasaribu, Ahmad Muchlisin Natas (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to determine the effect of dryland training on improving leg muscle endurance of swimming athletes at Clavo Swimming Club. The research method used was an experimental design with a two groups pretest-posttest design involving 20 swimming athletes divided into an experimental group and a control group. The experimental group received dryland training treatments including burpees, box jumps, and lunges jumps for 16 sessions, while the control group only performed regular swimming training. Leg muscle endurance was measured using a 25-meter swimming beep test with a kicking board. The results of the paired sample t-test showed a significant difference between pretest and posttest results in the experimental group, with a higher average increase compared to the control group. In addition, the independent sample t-test results also showed a significant difference between the experimental and control groups (p < 0.05). It can be concluded that dryland training has a significant effect on increasing leg muscle endurance of swimming athletes. These findings are expected to serve as input for coaches to optimize swimming training programs by incorporating structured dryland exercises.